2017
DOI: 10.5152/tjg.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

What is the long term acid inhibitor treatment in gastroesophageal reflux disease? What are the potential problems related to long term acid inhibitor treatment in gastroesophageal reflux disease? How should these cases be followed?

Abstract: Decreased acid secretion is thought to adversely affect the absorption of calcium and increase the risk of fracture by causing a decrease in bone density. The meta-analyses of observational studies conducted with heterogeneous populations showed that the risk of any fracture (OR: 1.29, 95% CI: 1.18-1.41) and hip fracture (OR: 1.23, 95% CI: 1.11-1.36) slightly increased with PPI depending on the dose and regardless of duration; but no risk increase was detected with H2RA use (1,2).There are meta-analyses with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Omeprazole and lansoprazole are the most commonly used PPIs to treat GERD symptoms. Although there is a risk of increased bacterial growth and spontaneous bacterial peritonitis with PPI therapy [24], they have been proven safe and effective to treat nonerosive reflux disease (NERD). None of the studies in our systematic review reported any serious adverse effects, which also provides evidence that omeprazole and lansoprazole are safe and effective to use at least for a short period.…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole and lansoprazole are the most commonly used PPIs to treat GERD symptoms. Although there is a risk of increased bacterial growth and spontaneous bacterial peritonitis with PPI therapy [24], they have been proven safe and effective to treat nonerosive reflux disease (NERD). None of the studies in our systematic review reported any serious adverse effects, which also provides evidence that omeprazole and lansoprazole are safe and effective to use at least for a short period.…”
Section: Discussionmentioning
confidence: 99%
“…Hatemi et al 12 concluded there is a risk for intestinal bacterial overgrowth in PPI users (level of evidence 2) and this should be considered in patients where such bacterial overgrowth might be a risk (level of evidence 5). Singh et al, 11 in turn, showed an association, but not causality, between PPI use and SIBO, and also pointed out contradictions in recent studies given the difference in types, number of participants and different diagnostic methods.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…[23][24][25][26][27] This increase is more likely related to the change in pH provided by the PPI than its dose or duration of use. Hatemi et al 12 also show a higher risk for CDI (level of evidence 3a), and treatment with PPI should not be discontinued when properly indicated (level of evidence 5). Savarino et al 15 add that CDI is a possible side effect of using PPIs, as they reduce the antibacterial effect of gastric acid.…”
Section: Enteric Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rejuvenation of the pathology may lead to an increase in the number of complications such as Barrett's esophagus and adenocarcinoma [11] due to a longer history, which also entails a longer treatment with proton pump inhibitors (PPIs). The metaanalysis showed that long-term use of PPIs increases the risk of fractures, bacterial overgrowth and spontaneous bacterial peritonitis, community-acquired pneumonia, and decreased zinc absorption [12].…”
Section: Problems Of Gastroesophageal Reflux Diseasementioning
confidence: 99%